As recentes alterações no currículo obrigatório de Geografia em Portugal (1989-2001) - Alegria, Maria Fernanda (2002)
RECENT CHANGES IN COMPULSORY SCHOOL EDUCATION CURRICULUM OF GEOGRAPHY IN PORTUGAL (1989-2001). The two recent reforms in compulsory school education in Portugal (decrees 286/89 and 6/2001) have affected geography teaching. Changes made between 1989 and 2001 included: setting up 90-minute classes with less geography teaching on a weekly basis; organising timetables with history classes; teaching geography at the 7th, 8th and 9th grade level since 2001,whereas in 1989 geography classes ceased at 8th grade. Curriculum contents were changed unlike what had been initially planned. The first part of the paper deals with the idea of ‘competence’, central to more recent educational reform, with a summary of the meaning of the three new so-called transversal curriculum items (civic training, project planning and structured learning), as well as with an understanding of the dissemination of educational reform throughout the country and the advantages and difficulties of schools being more autonomous in their curriculum organisation. The second part explores the usefulness of geography in compulsory education, the justification for some resources and an assessment ofthe qualities and difficulties of the 2001 reform.